Beyond Memorisation: Investigating the Influence of Open Inquiry on Chemistry Students’ Scientific Process Skills - Bamidele Emmanuel Tijani (Journal of Research in Environmental and Science Education, 2025)
The demand for 21st-century skills, particularly critical thinking, problem-solving, and scientific literacy, has necessitated a shift from traditional teacher-centred instruction to student-driven, inquiry-based learning. Open inquiry instructional strategy has been increasingly recognised for its potential to enhance students’ engagement and acquisition of process skills in science education. However, limited empirical evidence exists regarding its effectiveness in contexts where traditional methods still dominate. This study examined the effect of the open inquiry instructional strategy on the development of process skills in chemistry among secondary school students. A quasi-experimental research design was employed, involving a pre-test and post-test with a non-equivalent control group of 322 Senior Secondary School 1 (SSS1) students from six selected schools. Data were collected using the Chemistry Process Skills Assessment Test (CPSAT) and analysed using Analysis of Covariance (ANCOVA). The results revealed that students taught using open inquiry performed significantly better in process skills acquisition than those taught using the demonstration method (F(1, 319) = 74.305, p < .001, η² = .189). Additionally, while private school students had slightly higher mean scores than their public school counterparts, the difference was not statistically significant (F(1, 319) = 0.823, p = .365), suggesting that open inquiry is effective across different educational contexts. These findings highlight the need to integrate open inquiry into science curricula to promote active learning. The study recommends incorporating open inquiry into science curricula, providing teachers with targeted professional development, ensuring adequate laboratory resources, adopting a blended instructional approach, offering ongoing teacher support and mentorship, and conducting further research to explore its long-term impact and optimise its implementation.